2020
DOI: 10.4314/mejs.v12i1.1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Salt Stresses on Seed Germination and Early Seedling Growth of Camelina sativa L.

Abstract: Camelina sativa is a promising low-input, high yielding biodiesel crop that can be suitable to grow on marginal lands and is a good source of omega-3 fatty acids. But, saltiness is an overall issue of agriculture that constrains the germination, development and productivity of plant because of osmotic and ionic poisonous quality impacts. The aim of this study was to assess the effect of salinity (NaCl and KCl) on germination and early seedling growth of Camelina sativa. Camelina sativa seeds were obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…It has been reported that the germination speed decreases as NaCl and KCl concentrations increase in Camelina sativa (L.) Crantz. (Yohannes et al, 2020). It has been stated that increasing salinity decreases the germination speed in Lens culinaris Medic.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the germination speed decreases as NaCl and KCl concentrations increase in Camelina sativa (L.) Crantz. (Yohannes et al, 2020). It has been stated that increasing salinity decreases the germination speed in Lens culinaris Medic.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, chlorophyll a, chlorophyll b, and total chlorophyll contents decrease, leading to a decline in photosynthetic e ciency. Additionally, SS reduced the carotenoid pigments, which serve as protective agents against oxidative damage (Yohannes et al 2020;Waraich et al 2021). One of the major consequences of SS was the generation of reactive oxygen species (ROS) within plant cells.…”
Section: Introductionmentioning
confidence: 99%
“…There are numerous factors such as biotic and abiotic, that limit plant growth and development (Yohannes et al, 2020). The direct or indirect effects of climatic change are one of the abiotic factors that directly or indirectly affect crop yield (Billah et al, 2021;El Haddad et al, 2022).…”
Section: Introductionmentioning
confidence: 99%